Nutritional Status of Mediterranean Trees Growing in a Contaminated and Remediated Area - Domínguez, MaríaT; Marañón, Teodoro; Murillo, JoséM; Schulin, Rainer; Robinson, BrettH (Water, Air, and Soil Pollution, 2010)
t Soil contamination may contribute to forest decline, by altering nutrient cycling and acquisition by plants. This may hamper the establishment of a woody plant cover in contaminated areas, thus limiting the success of a restoration program. We studied the nutritional status of planted saplings of Holm oak (Quercus ilex subsp. ballota (Desf.) Samp.), white poplar (Populus alba L.), and wild olive tree (Olea europaea var. sylvestris Brot.) in the Guadiamar Green Corridor (SW Spain) and compared it with established adult trees. Soils in this area were affected by a mine-spill in 1998 and a subsequent restoration program. The spill resulted in soil acidification, due to pyrite oxidation, and deposited high concentrations of some trace elements. In some sites, we detected a phosphorus deficiency in the leaves of Q. ilex and O. europaea saplings, as indicated by a high N:P ratio (>16). For O. europaea, soil contamination explained 40% of the variability in leaf P and was negatively related to chlorophyll content. Soil pH was a significant factor predicting the variability of several nutrients, including Mg, P, and S. The uptake of Mg and S by P. alba was greater in acidic soils. The monitoring of soil pH is recommended since long-term effects of soil acidification may negatively affect the nutritional status of the trees
The following values have no corresponding Zotero field: publisher: Springer Netherlands
Keywords: Heavy metal; Olea europaea; phosphorus; Populus alba; Quercus ilex; soil remediation; Tree nutrition